A modified wire-loop snare technique for the retrieval of inferior vena cava filter with embedded hook. (1st December 2017) - Wang, Yuewei; Guan, Xiaomei; Wang, Haofu
Common obstacles to successful retrieval of retrievable inferior vena cave filter include embedded filter hook and severe tilt of the filter. We described a modified wire-loop snare technique using self-made fishhook-like pigtail catheter and 11-F-long sheath to retrieve a severe tilted filter with embedded hook successfully. The modified wire-loop snare technique is simple and effective requiring only standard equipment and single venous access. This technique may be suitable for some types of retrievable filter with embedded hook.